Molecular docking and dynamics studies of 8,9-dimethoxy ellagic acid contained in Peperomia pellucida (L.) Kunth against various diabetes mellitus receptors - Yasmiwar Susilawati; Raden Bayu Indradi; Aiyi Asnawi; Ellin Febrina (GarVal Editorial Ltda., 2024)
Context: The search for antidiabetic drugs that target the receptors involved in diabetes has received significant attention in recent years. Peperomia pellucida (L.) Kunth's ethanol extract and ethyl acetate fraction have antihyperglycemic activity. 8,9-dimethoxy ellagic acid (DEA) has shown significant diabetes mellitus activity in mice, but its interaction with diabetes receptors remains unknown. Aims: To perform molecular docking and molecular dynamics simulations to explore the binding interactions and stability of DEA within the binding sites of enzymes involved in diabetes. Methods: At the outset, the utilization of molecular docking was limited to forecasting the DEA's binding orientations and affinities within the active sites of the enzymes implicated in diabetes. Following this, molecular dynamics simulation was employed to investigate the interactions, stability, and dynamic behavior of these complexes over a period of 100 nanoseconds. Results: Molecular docking results revealed that DEA interacts with all selected receptors involved in diabetes and interacts more strongly with the aldose reductase receptor (PDB ID 3S3G) than the native ligand, with a binding energy of -10.3 kcal/mol. However, further molecular dynamics simulations confirmed the stability of the receptor complex with DEA over 100 ns, which is less potent than that of the native ligand. This is probably due to the rigidity of the DEA molecular structure. Conclusions: This study highlights the potential of DEA derived from P. pellucida as an inhibitor of various receptors involved in diabetes.